Benchmarking of Online Information Literacy Tutorials to Identify Lessons Learnt and Best Practice. - Hunn, Ruth A.; Elliott, Amanda C.; Town, J. Stephen (Cranfield University, 2005)
This paper reports the process and findings of a benchmarking exercise conducted on 10 online information literacy tutorials from around the English speaking World. The benchmarking exercise comprised site visits and the completion of an online survey. The aim of the exercise was to establish best practice and to gather any lessons that could be learnt, with the overall purpose of determining ways that our information literacy tutorial could provide the best quality and performance through the identification of user requirements. The method of selecting the tutorials to benchmark against and the areas to include in the review is described. A summary of results from each of the benchmarked areas is included for: pedagogical issues; design, development and user feedback; content; interactivity; and look and feel.
Keywords: Information literacy; Benchmarking; Tutorial design and development